Cognitive-behavioral treatment for social phobia in Parkinson’s disease: A single-case study - Heinrichs, Nina (2001)
Individuals with Parkinson’s disease often exhibit symptoms of social anxiety. However, they rarely meet criteria for social phobia due to the medical exclusion criteria of DSM-IV. The present study reports the case of a 60-year-old male with Parkinson’s disease who also met criteria for social phobia. After receiving 12 weekly cognitive-behavioral group sessions for social phobia, clinician ratings and self-report measures at post-treatment and 6-month follow-up showed a significant short-term and long-term reduction of his social anxiety. These findings suggest that cognitive-behavior therapy may be an effective treatment for social anxiety, even if these symptoms are related to Parkinson’s disease.